2018
DOI: 10.1016/j.ijid.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of dengue and its coinfections in Delhi

Abstract: Delhi being hyperendemic, the occurrence of concurrent infections with multiple DENV serotypes has become a frequent finding. The study emphasizes the need of epidemiological and entomological surveillance to monitor trends in dengue distribution, seasonal patterns and circulating serotypes to guide dengue control activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 22 publications
2
24
2
Order By: Relevance
“…15,16 Similarly, all the four serotypes were found to be circulating with predominance of DEN-2 along with concurrent infection with multiple serotypes during 2015. 17 In contrast, our study from central Delhi reveals predominance of DEN-3 followed by DEN-1. Thus, clearly demonstrating that the predominant serotypes might vary even within city.…”
Section: Discussioncontrasting
confidence: 80%
“…15,16 Similarly, all the four serotypes were found to be circulating with predominance of DEN-2 along with concurrent infection with multiple serotypes during 2015. 17 In contrast, our study from central Delhi reveals predominance of DEN-3 followed by DEN-1. Thus, clearly demonstrating that the predominant serotypes might vary even within city.…”
Section: Discussioncontrasting
confidence: 80%
“…Importantly, the expansion of CHIKV distribution and the establishment of local transmission hotspots in newly colonized areas pose a high risk of co‐infections with other highly prevalent tropical diseases. A number of epidemiological studies have reported co‐infections of CHIKV with pathogens such as Zika virus (ZIKV), dengue virus (DENV), and malaria parasites in humans although the pathological outcomes of these co‐infections have not been clearly defined. Particularly, different clinical reports from African malaria cohorts suggested the presence of CHIKV infections.…”
Section: Co‐infection With Plasmodium Parasites Modulates Chikv Pathomentioning
confidence: 99%
“…Importantly, the expansion of CHIKV distribution and the establishment of local transmission hotspots in newly colonized areas pose a high risk of co-infections with other highly prevalent tropical diseases. A number of epidemiological studies have reported co-infections of CHIKV with pathogens such as Zika virus (ZIKV), dengue virus (DENV), and malaria parasites in humans[76][77][78][79][80][81][82][83][84][85] although the F I G U R E 1 Malaria co-infection impairs CHIKV-specific CD4 + T cell responses in the pLN-footpad axis. In CHIKV-infected mice, virusspecific CD4 + T cells multiply in the popliteal lymph node (pLN) and acquire a Th1 phenotype.…”
mentioning
confidence: 99%
“…Aedes albopictus and Aedes aegypti are the main DF vectors in Guangzhou [10]. Referring to mosquito breeding and DF transmission, meteorological conditions [11,12] as well as human (demographic structure, population size) [13,14,15] and land-use factors (traffic, standing water) [16,17] have been identified as important factors affecting the transmission of DF disease. For example, mosquito breeding activities are affected by temperature: Aedes albopictus are most active in breeding activities when the temperature is between 26 °C and 30 °C, but the feeding activity of mosquitoes decreases and mortality increases when the temperature is lower than 15 °C or higher than 35 °C [12].…”
Section: Introductionmentioning
confidence: 99%